Women educational leaders and the empowerment of others - Muzvidziwa, Irene (2016)
Educational management has generally been organized in a hierarchical manner that place more men in leadership roles in which authority and power are highly structured. However, more women are entering leadership roles that traditionally have been preserved and occupied by men. Women’s approach to power and how they use it is of interest in this paper.This paper demonstrates how women primary school principals in the KwaZulu Natal (KZN) province in South Africa conceptualized power and utilized it to make things happen in their schools. A detailed description of the successes and challenges the women faced as KZN educational leaders is provided. A qualitative research design with an aspect of phenomenology was used to generate data. Analysis of data has been an ongoing process of identifying emerging patterns and themes. One of the major themes that emerged is that power is seen as a resource that enables communities and educational leaders to achieve their goals.